The Effect of Vitamin C and Antacid Tablets (SDI) on the Pharmacokinetics of Aspirin Tablets (SDI) in Human - Jaafar Jaber Ibraheem Al-Tamimi; Rihab A J. Altaii; Wedad K. Ali (College of Pharmacy / Mustansiriyah University, 2016)
The study explored the effect of vitamin c and antacid on the pharmacokinetics of aspirin in human subjects.  The study was conducted in 12 healthy adults volunteers who were asked to take in the first study, two tablets of aspirin (300 mg) alone. In a second study, the same subjects were given  two tablets of aspirin (300 mg) together with one tablet of vitamin c 500 mg. Eventually, in the third study,  the subjects were administered  two tablets of aspirin (300 mg) and one capsule containing NaHCO3 (500 mg). The three studies were separated by one week wash out period.  In each study, urine was collected from each individual participated in the study at specific time intervals for up to24 hours post dosing to calculate the cumulative amount of salicylate excreted in urine. The excretion rate was plotted against the mid-time sampling time to calculate the elimination rate constant (K), and the elimination half-life (T0.5).  It was found from the current investigation that administration of vitamin c tablet with aspirin tablets reduce (K) values and elongate T0.5, whereas, NaHCO3 intake elevate K values and reduce T0.5 in all subjects participated in the study.             It can be concluded from the current investigation that administration of weak acid drugs like vitamin c, or weak base drugs like antacid have considerable effect on the residence of aspirin in the body and consequently its intensity and duration of clinical effect.